Prospective comparison of early bone marrow evaluation on day 5 versus day 14 of the "3 + 7" induction regimen for acute myeloid leukemia. Issue 12 (17th November 2015) - Ofran, Yishai; Leiba, Ronit; Ganzel, Chezi; Saban, Revital; Gatt, Moshe; Ram, Ron; Arad, Ariela; Bulvik, Shlomo; Hellmann, Ilana; Gino‐Moor, Sharon; Zuckerman, Tsila; Hoffman, Ron; et al.
Abstract : Evaluation of early response during induction therapy for acute myeloid leukemia (AML) is used for prognostication and re‐induction strategy, yet the optimal evaluation time point is unknown. Clearance of bone marrow (BM) blasts by day 14 of therapy does not ensure remission; thus, some patients requiring re‐induction are neglected. This study aimed to examine the role of earlier BM evaluation during induction for predicting remission and overall survival. Results of BM testing on the 5th and 14th day of intensive induction were prospectively compared in 127 adult patients with AML. Re‐induction was given, based on Day 14 results, to 25 patients. Reduction of the BM blast count to <5% as early as by the fifth day of induction was more specifically associated with the achievement of remission compared to Day 14 (88.2% vs. 60%, respectively). Rapid responders have a better 3‐year overall survival (OS). Day 5 results are a stronger predictor of OS by multivariate analysis and better segregate long‐term survivors than the Day 14th BM count (66% vs. 30%, P = 0.0001 and 48% vs. 37%, respectively, P = 0.04). The Day 5 evaluation of BM carries significant clinical information. The benefit of prescribing re‐induction based on such early evaluation should be prospectively studied. Am. J. Hematol. 90:1159–1164, 2015. © 2015 Wiley Periodicals, Inc.